Stigma, medication adherence and coping mechanism among people living with HIV attending General Hospital, Lagos Island, Nigeria - Sekoni, Adekemi O. (Afr J Prim Health Care Fam Med, 2012)
BACKGROUND: People living with HIV and AIDS (PLWHA) experience some form of stigma which could lead to poor medication adherence. OBJECTIVES: This study assessed the various domains of stigma experienced by PLWHAs attending an HIV clinic at General Hospital, Lagos Island, their medication adherence patterns and their coping mechanisms for ensuring adherence to antiretroviral therapy. METHOD: A cross-sectional study design with a sample size of 200 was used. Respondents were selected using systematic random sampling. Interviewers administered structured questionnaires were used to collect information on the domains of stigma. Data was analysed using EPI info(©). This was followed by a focus group discussion (FGD) with seven participants at the clinic using an interview guide with open-ended questions. RESULTS: Overall, stigma was experienced by 35% of the respondents. Within this group, 6.6%, 37.1%, 43.1% and 98.0% of the respondents reported experiencing negative self image stigma, personalised stigma, disclosure stigma and public attitude stigma respectively. Almost 90% of the respondents were adherent. The FGD revealed that disclosure was usually confined to family members and the coping mechanism for achieving adherence was to put antiretroviral (ARVs) in unlabelled pill boxes. CONCLUSION: This study found that stigma was low and that the most common domain of stigma experienced was public attitude stigma. Medication adherence of respondents was good as a result of the coping mechanism, which involves putting ARVs in unlabelled pill boxes.